Generation of Uncorrelated Multichannel Chaos by Electrical Heterodyning for Multiple-Input–Multiple-Output Chaos Radar Application - Chih-Hao Cheng; Yi-Cheng Chen; Fan-Yi Lin (IEEE Photonics Journal)
Multiple-input–multiple-output (MIMO) radar has received much attention in recent years for its great ability in imaging. However, the essence of MIMO radar has not been fully implemented due to the lack of proper transmission waveforms. In MIMO radar, the transmission waveform of each channel has to be uncorrelated with one another to avoid cross-interference between channels. To achieve this, we investigate the generation of uncorrelated multichannel chaos using electrical heterodyning for MIMO chaos radar (MIMO CRADAR) application. By electrically heterodyning a seed chaos source with multiple single-frequency local oscillators, chaos with different heterodyned spectra can be extracted and converted into multiple chaos channels. In this paper, the correlations between different channels of chaos generated are analyzed both numerically and experimentally. The minimal frequency spacing of the local oscillators for generating the largest amount of uncorrelated chaos channels is discussed. In our analysis, thousands of uncorrelated chaos channels can be simultaneously generated with a correlation time of several microseconds. Moreover, compared with those conventional waveform-designing methods that require complicated optimization and digital-to-analog conversion (DAC), the proposed heterodyned technique shows, for the first time, that multiple uncorrelated channels can be generated in real-time while breaking the bandwidth limitation of the DAC devices. A proof-of-concept experiment is successfully demonstrated to show the feasibility of using multichannel heterodyned chaos in the MIMO CRADAR application.